2021
DOI: 10.1002/ange.202013731
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Chemically and Biologically Diverse Pyrroquinoline Pseudo Natural Products

Abstract: Natural product (NP) structures are a rich source of inspiration for the discovery of new biologically relevant chemical matter. In natural product inspired pseudo‐NPs, NP‐derived fragments are combined de novo in unprecedented arrangements. Described here is the design and synthesis of a 155‐member pyrroquinoline pseudo‐NP collection in which fragments characteristic of the tetrahydroquinoline and pyrrolidine NP classes are combined with eight different connectivities and regioisomeric arrangements. Cheminfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 43 publications
(70 reference statements)
1
1
0
Order By: Relevance
“…Thus, in the synthesis of PNPs following our analysis, the lack of stereochemical information has to be counterbalanced by the synthesis and biological evaluation of multiple stereoisomers. We note that in our related experimental work, we followed this guideline, see for instance Grigalunas et al, 34 Christoforow et al, 11 and Liu et al 35 These results demonstrate that PNPs, as defined by us, have, in fact, been synthesized for at least 45 years, and it can be concluded that they occur frequently among biologically relevant small molecules. The frequency of their occurrence in biologically relevant compounds is a testimony to their biological relevance and validates the PNP design principle as a successful and actually historically proven general concept for the discovery of new bioactive chemical matter and the exploration of biologically relevant chemical space.…”
Section: ■ Conclusionsupporting
confidence: 62%
“…Thus, in the synthesis of PNPs following our analysis, the lack of stereochemical information has to be counterbalanced by the synthesis and biological evaluation of multiple stereoisomers. We note that in our related experimental work, we followed this guideline, see for instance Grigalunas et al, 34 Christoforow et al, 11 and Liu et al 35 These results demonstrate that PNPs, as defined by us, have, in fact, been synthesized for at least 45 years, and it can be concluded that they occur frequently among biologically relevant small molecules. The frequency of their occurrence in biologically relevant compounds is a testimony to their biological relevance and validates the PNP design principle as a successful and actually historically proven general concept for the discovery of new bioactive chemical matter and the exploration of biologically relevant chemical space.…”
Section: ■ Conclusionsupporting
confidence: 62%
“…[6][7][8][9] The tetrahydroquinoline (THQ) motif is an important structural scaffold of many natural products and medicinal agents that have demonstrated a variety of biological activities. 10,11 Due to their widespread existence in natural products and pharmaceutical agents, a number of methods have been developed for the construction of THQ skeleton. [12][13][14] Among them, the photochemical approach mediated by visible light offered a more sustainable methodology in this process.…”
Section: Introductionmentioning
confidence: 99%